Importance of microgreen storage conditions: Bibliometric analysis and literature review (Research, Society and Development, 2022)
Microgreens are young plants that basically consist of three parts: a central stem, cotyledon leaves, and a pair of true leaves. They can be grown organically and harvested between 1-2 weeks after sowing. Microgreens concentrate 40 times more nutrients than mature vegetables, presenting a greater amount of nutrients and micronutrients. However, microgreens face various conservation and durability problems due to their difficult storage, as they have fragile leaves, with ease of wilting and early senescence. Therefore, they need packaging that facilitates their breathing and maintains their visual quality, since their consumption is often governed by their appearance. In this context, the present work aimed to carry out a bibliometric analysis and literature review about the importance of storing microgreens, bringing recent studies with techniques that have been studied and have shown promising results. It was found that the use of chlorinated solutions and organic acids has great potential to increase the shelf life of microgreens, in addition, most studies used OTR (oxygen transmission rate) film packaging, or polyethylene/vacuum packaging, with refrigeration temperatures ranging from 1 to 10 ºC, where the temperature of 5 ºC proved to be the most ideal to increase the shelf life of most microgreens.